Maximising allied health accessibility for Aboriginal and Torres Strait Islander children: exploring experiences and perceptions of a family-centred consultation model. (3rd April 2022) - Sargison, Helen; Fernandez, Yolanda; Marsh, Bonny; Ferguson, Josephine; Foley, Wendy; Askew, Deborah; Tyson, Claudette; Rose, Tanya; Scarinci, Nerina; Copley, Jodie
ABSTRACT: Background : Otitis media prevalence is high for Australian Aboriginal and Torres Strait Islander children and associated with developmental impacts. Access to allied health services can also be challenging for Aboriginal and Torres Strait Islander families. To address this, the Family-Centred Consultation Model (FCCM) was developed. The FCCM involved three main components in a 'cycle of care': (1) a pre-session phone-call between the allied health professional (AHP) and parent/carer; (2) a face-to-face session; and (3) a follow-up phone-call. Method: The FCCM was trialled in a hearing and development clinic incorporating audiology, speech pathology and occupational therapy services, and co-located within an Aboriginal and Torres Strait Islander primary health service. This study used a qualitative description approach to explore the perceptions and experiences of parents/carers ( n = 11) and AHPs ( n = 3) in accessing or delivering services using the FCCM. Results: Parents/carers felt comfortable with the FCCM and perceived it to be responsive to their needs. AHPs perceived it was both rewarding and challenging, and enabled holistic, flexible and customised services. Conclusion: This study highlights the potential for brief intervention and family-centred approaches to enhance service accessibility for some Aboriginal and Torres Strait Islander consumers.